Assessing the Potential of Sponges (Porifera) as Indicators of Ocean Dissolved Si Concentrations - Alvarez, Belinda; Frings, Patrick J.; Clymans, Wim; Fontorbe, Guillaume; Conley, Daniel J. (Frontiers in Marine Science, 2017)
We explore the distribution of sponges along dissolved silica (dSi) concentration gradients to test whether sponge assemblages are related to dSi and to assess the validity of fossil sponges as a palaeoecological tool for inferring dSi concentrations of the past oceans. We extracted sponge records from the publically available Global Biodiversity Information Facility (GBIF) database and linked these records with ocean physiochemical data to evaluate if there is any correspondence between dSi concentrations of the waters sponges inhabit and their distribution. Over 320,000 records of Porifera were available, of which 62,360 met strict quality control criteria. Our analyses was limited to the taxonomic levels of family, order and class. Because dSi concentration is correlated with depth in the modern ocean, we also explored sponge taxa distributions as a function of depth. We observe that while some sponge taxa appear to have dSi preferences (e.g. class Hexactinellida occurs mostly at high dSi), the overall distribution of sponge orders and families along dSi gradients is not sufficiently differentiated to unambiguously relate dSi concentrations to sponge taxa assemblages. We also observe that sponge taxa tend to be similarly distributed along a depth gradient. In other words, both dSi and/or another variable that depth is a surrogate for, may play a role in controlling sponge spatial distribution and the challenge is to distinguish between the two. We conclude that inferences about palaeo-dSi concentrations drawn from the abundance of sponges in the stratigraphic records must be treated cautiously as these animals are adapted to a great range of dSi conditions and likely other underlying variables that are related to depth. Our analysis provides a quantification of the dSi ranges of common sponge taxa, expands on previous knowledge related to their bathymetry preferences and suggest that sponge taxa assemblages are not related to particular dSi conditions.